2018
DOI: 10.1186/s12944-018-0861-y
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride to high density lipoprotein cholesterol ratio among adolescents is associated with adult hypertension: the Kangwha study

Abstract: BackgroundThe triglyceride to high density lipoprotein cholesterol (TG/HDL-C) ratio associated with hypertension in adults. However, whether the TG/HDL-C ratio in adolescents predicts future hypertension remains unclear. Here, we evaluated the prospective association between the TG/HDL-C ratio in adolescents and hypertension in early adulthood.MethodsThe Kangwha Study is an ongoing prospective cohort study that has tracked the blood pressure of first grade elementary school students since 1986. We followed up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 23 publications
(31 reference statements)
2
17
0
2
Order By: Relevance
“…Findings showed lower BMI reduced the risk of developing hypertension 43 . In recent years, a number of studies have shown that TG, HDL, LDL and TG can be used as predictors of essential hypertension events by constructing different models [44][45][46][47][48][49] . Fottrell et al surveyed a random sample of 12,280 adults >30 years old in 96 villages in rural Bangladesh and found that obesity, smoking, passive smoking and increased salt consumption were risk factors for hypertension 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Findings showed lower BMI reduced the risk of developing hypertension 43 . In recent years, a number of studies have shown that TG, HDL, LDL and TG can be used as predictors of essential hypertension events by constructing different models [44][45][46][47][48][49] . Fottrell et al surveyed a random sample of 12,280 adults >30 years old in 96 villages in rural Bangladesh and found that obesity, smoking, passive smoking and increased salt consumption were risk factors for hypertension 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Se ha propuesto el índice Tg/HDL-C como un indicador efecti vo de adolescentes de 10 a 14 años que están en riesgo de desarrollar enfermedad cardiometabólica 24 e hipertensión arterial 25 . Diversos estudios han sugerido y usado diferentes puntos de corte para defi nir este índice como alto.…”
Section: Discussionunclassified
“…This ratio is related to disorders and diseases of metabolism. During the 20-year follow-up found that to group with high triglyceride/HDL ratio is likely to have hypertension when compared with the group that has low ratio triglyceride/HDL ratio [14].…”
Section: Ratio Of Triglyceride/hdl Is the Ratio Between The Values Ofmentioning
confidence: 96%